Influence of moisture content and type of package on the preservation of Brachiaria brizantha seeds - Aparecida Previero, Conceição; Fernandes Razera, Luiz; Groth, Doris (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this work was to evaluate the physiological quality of Brachiaria brizantha seeds for 18 months of storage in an open storage condition of Campinas, SP, Brazil. Seeds from a seed lot, treated or not with sulphuric acid, were packed with 6-7%, 10-11% and 13-14% moisture content in paper bags and polyethylene bags. The experimental design was a completely randomized arranged in a factorial 2 x 2 x 3 x 7. The results showed that: a) the seed moisture content was kept relatively constant throughout the experimental period for the seeds packed in polyethylene bags, while the moisture contents of seeds packed in paper bags reached the equilibrium moisture content with the relative humidity of the storehouse; b) the physiological quality of the seeds packed in polyethylene bags decreased faster than any other experimental condition; c) by the end of the experiment, seed germination was about the same for the seeds stored with 10-11% and 6-7% moisture content in the polyethylene bags; d) best results of seed germination and vigor were obtained with the seeds dried to 6-7% moisture content, and packed in polyethylene bags; e) seeds treated with sulfuric acid consistently showed greater losses of viability than non-treated seeds.
Keywords: storage